Pediatric heart transplantation after a Fontan procedure - D. V. Ryabtsev; A. S. Ivanov; M. T. Bekov; E. A. Spirina; V. N. Poptsov; E. S. Kavardakova; A. Ch. Chartaev; S. V. Gautier (Вестник трансплантологии и искусственных органов)
The Fontan procedure is a surgical technique used for hemodynamic correction of complex congenital heart defects (CHDs), and is used when radical correction of CHDs is anatomically impossible. In the long term – from 10 to 20 years – Fontan circulation can lead to «failing Fontan» characterized by heart failure symptoms, requiring adjustments to medical treatment and potentially surgical interventions, including heart transplantation (HT). Foreign studies indicate that HT is an effective method for prolonging life in patients with failing Fontan circulation. It stabilizes the patient’s condition. This paper presents the first documented case of HT in a child following a Fontan procedure in the Russian Federation.